Enhancing critical thinking through guided discovery learning in distance medical education in Papua - Samdei Carolina Rumbino; Elisa Nugraha Haryadi Salakay; Doni Widyandana; Titi Savitri Prihatiningsih (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Medical education in Papua faces unique challenges, especially in enhancing students’ critical thinking through distance learning. This study aimed to develop a Guided Discovery Learning (GDL)-based student worksheet and evaluate its effectiveness in improving critical thinking skills. Employing a Research and Development (R&D) design with a mixed-method approach that integrated both quantitative and qualitative data. The study involved 184 first, third, fifth, and seventh-semester medical students in Papua. Instruments included validated critical thinking tests based on Facione’s indicators, worksheet assessment rubrics, and student response questionnaires. Data were analyzed using paired sample t-tests and thematic analysis. The results showed a significant increase in student’s critical thinking post-test scores (mean = 62.45) compared to pre-test scores (mean = 37.00). Students also gave positive responses to the GDL-based worksheets. This indicates that GDL-based worksheets are effective instructional tools for fostering critical thinking in remote education settings. The study contributes to educational practice by introducing an adaptable method suitable for under-resourced regions. However, limitations include infrastructural barriers and a small sample size, which may affect generalizability. Future research should involve a broader population and explore long-term impacts.